2014
DOI: 10.1515/hsz-2014-0170
|View full text |Cite
|
Sign up to set email alerts
|

Twin-arginine translocation-arresting protein regions contact TatA and TatB

Abstract: Tat systems translocate folded proteins across biological membranes of prokaryotes and plant plastids. TatBC complexes recognize N-terminal Tat signal peptides that contain a sequence motif with two conserved arginines (RR-motif), and transport takes place after a recruitment of TatA. Unfolded Tat substrate domains lower translocation efficiency and too long linkers lead to translocation arrest. To identify the components that interact with transported proteins during their passage through the translocon, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…To finally examine whether transport-compromising exchanges on the HiPIP surface did indeed reduce the TatA contacts in vivo , we carried out an in vivo cross-link experiment and monitored the TatA interactions with the signal peptide and the mature domain of HiPIP with or without the P104D exchange. We placed p Bpa either at position A13 of the signal peptide or at position I52 of the mature domain, which was recently shown by us to contact TatA and TatB in vivo [45]. While the signal peptide interaction with TatA was unaffected by the P104D exchange, the I52 p Bpa cross-link to TatA was clearly reduced, and this reduction was independent of TatBC (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…To finally examine whether transport-compromising exchanges on the HiPIP surface did indeed reduce the TatA contacts in vivo , we carried out an in vivo cross-link experiment and monitored the TatA interactions with the signal peptide and the mature domain of HiPIP with or without the P104D exchange. We placed p Bpa either at position A13 of the signal peptide or at position I52 of the mature domain, which was recently shown by us to contact TatA and TatB in vivo [45]. While the signal peptide interaction with TatA was unaffected by the P104D exchange, the I52 p Bpa cross-link to TatA was clearly reduced, and this reduction was independent of TatBC (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…An APH interaction with mature domains of Tat substrates had been for the first time experimentally demonstrated by the group of Carole Dabney Smith for the thylakoidal system (46). Also in the E. coli system, mature domains of Tat substrates have been shown to interact with TatA (16,[47][48][49], and it has been demonstrated that TatA has the capacity to interact with Tat substrates in a TatBC independent manner (26). For the thylakoid system it has been suggested that the APH interactions relate to nonspecific passive contacts before or during the membrane passage of mature domains, as a crosslink to a position at the end of the APH (Phe-48) was .…”
mentioning
confidence: 99%
“…Based on the substrateindependent TatA/TatBC interactions, we currently favor the view that TatA and TatBC always function hand in hand and remain in close proximity. The RR-motif of Tat signal peptides can remain associated with TatC during translocation (15), and Tat substrates are contacting TatA during transport with their mature domains (46,49,26). TatA recognizes the transported domains to initiate the conformational switch, but TatBC recognizes the RR-motif and transport is only achieved when both activities cooperate.…”
mentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 18 Expression of these variants results in efficient export of all three mutants, indicating that these changes are tolerated by the proofreading system. Export of 5N-Leu and 6N-Leu appears at first sight to be less efficient, in that the blot signals are slightly weaker for the periplasmic band.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This did raise the possibility that Tat proofreading assesses whether a substrate should be transported based on its hydrophobicity, as such residues would usually be sequestered inside correctly folded substrates. Several studies have built on the work presented by Richter et al, utilising long sections of FG repeats [17] [18] or (Gly 4 /Ser) linkers to separate two folded domains or inserted after the signal peptide, both of which intrinsically lack structure. In these studies, translocation was observed to varying degrees, attributed to the physical length of substrate rather than any proofreading mechanism.…”
Section: Accepted Manuscriptmentioning
confidence: 99%